The Effect Of Using Wordwall Assisted Flashcards In Students’ Procedure Text Reading Achievement - Nathasya Alaina Nurylah; Mochamad Hatip; Kristi Nuraini (SS&H: Studies in Social Sciences and Humanities, 2024)
Finding out the element that influence reading achievement in a second/foreign language (L2) is essential for L2 teachers to improve learners’ L2 reading skills. Some studies had conducted to investigate the factors in term of learning media particularly flashcard that has an impact on reading comprehension. However, flashcard media has a variety to implement in learning process such as wordwall assisted flashcard. The current study fills this gap by examining the relationship between that learning media and reading comprehension in English as a Foreign Language (EFL). The base allegation of this study is that flash cards as learning media may have an impact on students’ reading comprehension to grasp the information in a procedure text. Two kinds of procedure text were used on reading reading tests (pre-test and post-test) that was accomplished by fourty seven EFL students. They were divided into two classes to find the difference in reading abilities of students who were treated using flashcards and students who were not. The results from the two tests will be compared to determine the impact of using flashcard as learning media on students' reading comprehension. The statistical analysis's findings showed significant differences in EFL reading comprehension according to test score, indicating that wordwall assisted flashcard  plays a crucial role in shaping EFL learners’ reading achievement. These results provide insightful information on how flashcards as learning media might be implemented and organized to support L2 learners in enhancing their L2 reading skills. The study infers with a few suggestions for further study in the areas of flashcards as L2 learning media and L2 reading.